Differential impact of minimum unit pricing on alcohol consumption between Scottish men and women: controlled interrupted time series analysis - Peter Anderson; Eileen F S Kaner; Jakob Manthey; Jürgen Rehm; Amy O'Donnell; Eva Jané Llopis (BMJ Open)
Objective To assess the immediate impact of the introduction of minimum unit pricing (MUP) in Scotland on alcohol consumption and whether the impact differed by sex, level of alcohol consumption, age, social grade and level of residential deprivation of respondents.Design Primary controlled interrupted time series analysis and secondary before-and-after analysis of the impact of introducing MUP in Scotland using alcohol consumption data for England as control.Setting Data from Kantar Worldpanel’s Alcovision survey, a continuous retrospective online timeline follow-back diary survey of the previous week’s alcohol consumption.Participants 53 347 women and 53 143 men.Interventions Introduction of a minimum price of 50 pence per UK unit (6.25 pence/g) for the sale of alcohol in Scotland on 1 May 2018.Main outcome measures Number of grams of alcohol consumed per week, in total, in off-trade (eg, at home) and in on-trade (eg, in pubs, restaurants).Results Primary interrupted time series analyses found that the introduction of MUP was associated with a drop in reported weekly total alcohol consumption of 5.94 g (95% CI 1.29 to 10.60), a drop in off-trade consumption of 3.27 g (95% CI −0.01 to 6.56) and a drop in on-trade consumption of 2.67 g (95% CI −1.48 to 6.82). Associated reductions were larger for women than for men and were greater among heavier drinkers than for lighter drinkers, except for the 5% of heaviest drinking men for whom an associated increase in consumption was found. Secondary before-and-after analyses found that reductions in consumption were greater among older respondents and those living in less deprived areas. The introduction of MUP was not associated with a reduction in consumption among younger men and men living in more deprived areas.Conclusions Greater policy attention needs to be addressed to the heaviest drinking men, to younger men and to men who live in more deprived areas.